Positive electrode active material layer, electrode, and solid-state battery
By using vinylidene fluoride copolymer as the adhesive in the positive electrode active material layer, the problem of insufficient adhesion between the positive electrode active material layer and the current collector is solved, and the charging and discharging efficiency and battery performance are improved.
Patent Information
- Application Number
- CN202380054086.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-20
- Publication Date
- 2025-02-28
AI Technical Summary
In the positive electrode active material layer containing a solid electrolyte, insufficient adhesiveness leads to poor adhesion between the positive electrode active material layer and the current collector, which affects the charge and discharge efficiency.
By using a vinylidene fluoride copolymer containing structural units derived from vinylidene fluoride and other monomers as the binder in the positive electrode active material layer, the adhesion between the positive electrode active material layer and the current collector is improved.
High adhesion between the positive electrode active material layer and the current collector is achieved, and the charging and discharging efficiency and the overall performance of the battery are improved.
Smart Images

Figure CN119547215A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode active material layer, an electrode and a solid-state battery. Background Art
[0002] In the previous secondary batteries containing electrolytes, when the battery cell is abnormal such as an internal short circuit of the battery cell or the temperature of the battery cell rises, the possibility of fire is extremely high. Therefore, from the perspective of improving the safety of the battery cell, research has been conducted on semi-solid batteries or all-solid batteries that convert most or all of the electrolyte into a solid electrolyte. Semi-solid batteries or all-solid batteries are considered to simplify safety devices and have excellent manufacturing costs and productivity because the electrolyte containing a flammable organic solvent is very small or zero.
[0003] The active material layer of the electrode of a semi-solid battery or an all-solid battery is assumed to contain a solid electrolyte in addition to the active material, conductive additive, and binder constituting the electrode active material layer of a conventional secondary battery.
[0004] For example, Patent Document 1 discloses that a positive electrode active material layer contains a positive electrode active material, a solid electrolyte, and an ionic liquid, and uses PVDF as a binder, thereby suppressing output reduction in an all-solid-state battery and suppressing a reduction in charge capacity as the positive electrode potential increases.
[0005] In addition, for example, Patent Document 2 discloses that a positive electrode active material layer contains a positive electrode active material, a solid electrolyte, LiFSI and LiPF as an ionic liquid. 6 , contains PVDF as a binder, which can inhibit the corrosion of the collector foil and achieve high charge and discharge efficiency.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-113444
[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-126807 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, according to the research of the inventors, if the positive electrode binder used in the previous secondary battery containing an electrolyte is used for the positive electrode, and the positive electrode has a positive electrode active material layer containing a solid electrolyte, sometimes the adhesion between the positive electrode active material layer and the collector is insufficient. It is believed that this is due to the insufficient adhesion of the positive electrode binder used in the previous secondary battery to the solid electrolyte. If the adhesion between the positive electrode active material layer and the collector is poor, it is difficult to stably achieve various required characteristics such as high charge and discharge efficiency. Therefore, even if it is a positive electrode with a positive electrode active material layer containing a solid electrolyte, it is also required to improve the technology of adhesion between the positive electrode active material layer and the collector.
[0012] The present invention is completed in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material layer that can form a positive electrode with excellent adhesion between the positive electrode active material layer and the collector, an electrode having the positive electrode active material layer, and a semi-solid battery or all-solid battery having the electrode.
[0013] Technical Solution
[0014] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by including a specific vinylidene fluoride copolymer as a binder in a positive electrode active material layer containing a positive electrode active material and a solid electrolyte, thereby completing the present invention.
[0015] The embodiment of the present invention relates to the following positive electrode active material layer, electrode, and semi-solid-state battery or all-solid-state battery, which contain a positive electrode active material (A), a solid electrolyte (B), and a binder (C).
[0016] [1] A positive electrode active material layer comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein the binder (C) is a vinylidene fluoride copolymer comprising a structural unit (Ca) derived from vinylidene fluoride and a structural unit (Cb) derived from a monomer other than vinylidene fluoride, the structural unit (Cb) derived from a monomer other than vinylidene fluoride contains a structural unit derived from the following compound, the compound being at least one selected from an unsaturated dibasic acid, an unsaturated dibasic acid monoester and a compound represented by the following formula (C-1), and when all the structural units contained in the vinylidene fluoride copolymer are set to 100.0% by mass, the structural unit (Ca) derived from vinylidene fluoride is 90.0% by mass or more.
[0017] [Chemical formula 1]
[0018]
[0019] (In formula (C-1), R 1 , R 2 and R 3are independently a hydrogen atom, a chlorine atom or an alkyl group having 1 to 5 carbon atoms, X 1 It is an atomic group with a molecular weight of 472 or less, the main chain of which is composed of 1 to 19 atoms, and contains at least one heteroatom selected from oxygen atoms and nitrogen atoms)
[0020] [2] The positive electrode active material layer according to [1], wherein the intrinsic viscosity of the vinylidene fluoride copolymer is 2.3 dL / g or more.
[0021] [3] The positive electrode active material layer according to [2], wherein the vinylidene fluoride copolymer contains a structural unit derived from hexafluoropropylene as a structural unit different from the structural unit (Cb), and when all the structural units contained in the vinylidene fluoride copolymer are set to 100.0 mass%, the structural unit derived from hexafluoropropylene is 2.0 mass% or more and 8.0 mass% or less.
[0022] [4] The positive electrode active material layer according to any one of [1] to [3], wherein the structural unit (Cb) derived from a monomer other than vinylidene fluoride contains the structural unit derived from an unsaturated dibasic acid monoester, and the unsaturated dibasic acid monoester is monomethyl maleate.
[0023] [5] The positive electrode active material layer according to any one of [1] to [4], wherein the solid electrolyte (B) is an oxide-based solid electrolyte.
[0024] [6] The positive electrode active material layer according to [5], wherein the solid electrolyte (B) contains a material represented by the following formula (B-1).
[0025] Li 1+x+y Al x Ti 2x Si y P 3y O 12 ……(B-1)
[0026] (In formula (B-1), x and y satisfy 0≤x≤1, 0≤y≤1).
[0027] [7] The positive electrode active material layer according to any one of [1] to [6], wherein the positive electrode active material (A) contains lithium metal phosphate, and the lithium metal phosphate is selected from LiFePO 4 、LiMnPO 4 、LiCoPO 4 and LiNiPO 4 In the group formed.
[0028] [8] An electrode comprising a current collector and the positive electrode active material layer according to any one of [1] to [7].
[0029] [9] A semi-solid-state battery or an all-solid-state battery comprising the electrode described in [8].
[0030] Beneficial Effects
[0031] According to the present invention, there can be provided a positive electrode active material layer capable of forming a positive electrode having excellent adhesion between the positive electrode active material layer and a current collector, an electrode including the positive electrode active material layer, and a semi-solid battery or all-solid battery including the electrode. DETAILED DESCRIPTION
[0032] 《Positive electrode active material layer》
[0033] The positive electrode active material layer contains a positive electrode active material (A), a solid electrolyte (B) and a binder (C).
[0034] The binder (C) contained in the positive electrode active material layer is a vinylidene fluoride copolymer containing a structural unit (Ca) derived from vinylidene fluoride and a structural unit (Cb) derived from a monomer other than vinylidene fluoride.
[0035] The structural unit (Cb) derived from a monomer other than vinylidene fluoride includes a structural unit derived from at least one selected from an unsaturated dibasic acid, an unsaturated dibasic acid monoester, and a compound represented by the following formula (C-1) described later.
[0036] In the vinylidene fluoride copolymer, when all the structural units contained in the vinylidene fluoride copolymer are taken as 100.0 mass %, the structural unit (Ca) derived from vinylidene fluoride accounts for 90.0 mass % or more.
[0037] By making the positive electrode active material layer contain the specific binder (C), an electrode having excellent adhesion between the positive electrode active material layer and the current collector can be formed.
[0038] Hereinafter, essential or optional components contained in the positive electrode active material layer will be described.
[0039] <Positive Electrode Active Material (A)>
[0040] The positive electrode active material (A) is not particularly limited, and for example, a conventionally known positive electrode active material can be used. As the positive electrode active material, a lithium-based positive electrode active material containing at least lithium is preferred. Examples of the lithium-based positive electrode active material include: x M y O z(M is a transition metal element, x = 0.02 to 2.2, y = 1 to 2, z = 1.4 to 4) represented by a positive electrode active material. In the above general formula, M can be at least one selected from the group consisting of Co, Mn, Ni, V, Fe and Si, or at least one selected from the group consisting of Co, Ni and Mn. As such a positive electrode active material, specifically, LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4 , Li 2 FeSiO 4 , Li 2 MnSiO 4 wait.
[0041] In addition, as the above general formula Li x M y O z The positive electrode active material (A) other than lithium titanate (e.g. Li 4 Ti 5 O 12 ), lithium metal phosphate (LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 ), transition metal oxides (V 2 O 5 、MoO 3 )、TiS 2 、LiCoN、Si、SiO 2 , Li 2 SiO 3 , Li 4 SiO 4 and lithium storage intermetallic compounds (such as Mg 2 Sn、Mg 2 Ge、Mg 2 Sb、Cu 3 Among them, lithium phosphate is preferred, and among lithium phosphate, LiFePO is preferred. 4 .
[0042] The shape of the positive electrode active material (A) is not particularly limited, and may be, for example, a particle shape or a thin film shape. From the viewpoint of good handling properties, the positive electrode active material (A) may be a particle shape.
[0043] When the positive electrode active material is in the form of particles, the average particle size (D50) of the particles is, for example, preferably 1 nm or more and 100 μm or less, and more preferably 10 nm or more and 30 μm or less.
[0044] From the viewpoint of suppressing the reaction between the positive electrode active material and the solid electrolyte, a coating layer containing a Li ion conductive oxide may be formed on the surface of the positive electrode active material (A).
[0045] Examples of Li ion conductive oxides include LiNbO 3 , Li 4 Ti 5 O 12 and Li 3 PO 4 wait.
[0046] The lower limit of the thickness of the coating layer is preferably 0.1 nm or more, and more preferably 1 nm or more. The upper limit of the thickness of the coating layer is preferably 100 nm or less, and more preferably 20 nm or less.
[0047] The content of the positive electrode active material (A) is not particularly limited, but is preferably 50% by mass or more and 98% by mass or less, more preferably 60% by mass or more and 95% by mass or less, and further preferably 70% by mass or more and 90% by mass or less, relative to 100% by mass of the positive electrode active material layer.
[0048] <Solid Electrolyte (B)>
[0049] As the solid electrolyte (B), a sulfide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used. Among them, an oxide-based solid electrolyte is preferably used from the viewpoint of safety and stability of the electrolyte.
[0050] Examples of sulfide-based solid electrolytes include Li 2 S-SiS 2 、LiI-Li 2 S-SiS 2 、LiI-Li 2 SP 2 S 5 、LiI-Li 2 O-Li 2 SP 2 S 5 、LiI-Li 2 SP 2 O 5、LiI-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 and Li 3 PS 4 wait.
[0051] Examples of oxide-based solid electrolytes include LLTO-based compounds ((La, Li)TiO 3 )、Li 6 La 2 CaTa 2 O 12 , Li 6 La 2 ANb 2 O 12 (A: alkaline earth metal), Li 2 Nd 3 T8h 12 , Li 3 BO 2.5 N 0.5 , Li 9 SiAlO 8 LAGP compounds (Li 1+x Al x Ge 2-x (PO4) 3 (0≤x≤1))、Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 Such LATP compounds (Li 1+ x Al x Ti 2-x (PO 4 ) 3 (0≤x≤1))、Li 1+x Ti 2-x Al x Si y (PO 4 ) 3-y (0≤x≤1,0≤y≤1), Li 1+y Al x M 2-x (PO 4 ) 3 (M is one or more elements selected from the group consisting of Ti, Ge, Sr, Sn, Zr and Ca, 0≤x≤1, 0≤y≤1), LiTix Zr 2-x (PO 4 ) 3 (0≤x≤1), LISICON(Li 4-2x Zn x GeO 4 (0≤x≤1)), LIPON compounds (Li 3+ y PO 4-x N x (0≤x≤1, 0≤y≤1)), NASICON compounds (LiTi 2 (PO 4 ) 3 etc.), garnet compounds (Li 7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 (0≤x≤1) etc.
[0052] Among oxide-based solid electrolytes, LATP-based compounds are preferred from the viewpoint of having high lithium ion conductivity. As the LATP-based compound, a LATP-based compound containing a material represented by the following formula (1) is preferred:
[0053] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 ……(1)
[0054] (In formula (1), x and y satisfy 0≤x≤1, 0≤y≤1).
[0055] In addition, examples of preferred oxide-based solid electrolytes other than the above-mentioned LATP-based compounds include: Li 7 La 3 Zr 2 O 12 (LLZO), Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO), Li 0.33 La 0.56 TiO 3 (LLTO), Li 1.6 Al 0.6 Ge1.4 (PO 4 ) 3 (LAGP) etc.
[0056] The content of the solid electrolyte (B) is not particularly limited, but is preferably 1% by mass or more and 40% by mass or less, more preferably 2% by mass or more and 30% by mass or less, and further preferably 3% by mass or more and 20% by mass or less, relative to 100% by mass of the positive electrode active material layer.
[0057] <Binder (C)>
[0058] The binder (C) is a vinylidene fluoride copolymer containing a structural unit (Ca) derived from vinylidene fluoride and a structural unit (Cb) derived from a monomer other than vinylidene fluoride.
[0059] The structural unit (Cb) derived from a monomer other than vinylidene fluoride includes a structural unit derived from at least one selected from an unsaturated dibasic acid, an unsaturated dibasic acid monoester, and a compound represented by the formula (C-1) described later.
[0060] When all the structural units contained in the vinylidene fluoride copolymer are taken as 100.0 mass %, the structural unit (Ca) derived from vinylidene fluoride accounts for 90.0 mass % or more.
[0061] The binder (C) is used to improve the adhesion between the solid electrolyte and other components (current collector, active material, conductive additive, etc.).
[0062] Examples of the unsaturated dibasic acid that provides the structural unit (Cb) include fumaric acid, maleic acid, citraconic acid, and phthalic acid.
[0063] Examples of the unsaturated dibasic acid monoester providing the structural unit (Cb) include monomethyl fumarate, monoethyl fumarate, monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, monoethyl citraconic acid, monomethyl phthalate, and monoethyl phthalate.
[0064] The compound represented by the formula (C-1) which provides the structural unit (Cb) is shown below.
[0065] [Chemical formula 2]
[0066]
[0067] In formula (C-1), R 1 , R 2 and R 3 are independently a hydrogen atom, a chlorine atom or an alkyl group having 1 to 5 carbon atoms, X 1An atomic group having a molecular weight of 472 or less and a main chain composed of 1 to 19 atoms, and containing at least one heteroatom selected from oxygen atoms and nitrogen atoms.
[0068] The compound represented by the above formula (C-1) is preferably a compound represented by the following formula (C-2).
[0069] [Chemical formula 3]
[0070]
[0071] In formula (C-2), R 1 , R 2 and R 3 Same as the above formula (C-1), X 2 An atomic group having a molecular weight of 456 or less and a main chain composed of 1 to 18 atoms.
[0072] In the formulas (C-1) and (C-2), from the viewpoint of polymerization reactivity, R is particularly preferably 1 , R 2 It is a substituent having little steric hindrance, preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom or a methyl group.
[0073] In formula (C-1), X 1 The molecular weight of the atomic group represented is 472 or less, preferably 172 or less. 1 The lower limit of the molecular weight of the atomic group represented by is not particularly limited, and X is usually -CH 2 -, i.e., the molecular weight is 14. In formula (C-2), X 2 The molecular weight of the atomic group represented is 456 or less, preferably 156 or less. 2 The lower limit of the molecular weight of the atomic group represented by is not particularly limited, but is usually 2 -CH 2 - form, that is, the molecular weight is 14.
[0074] From the viewpoint of polymerizability, X is preferably 1 or X 2 The molecular weight of the indicated atomic group is within the above-mentioned range.
[0075] Examples of the compound represented by formula (C-2) include carboxyethyl 2-acrylate, carboxyethyl 2-methacrylate, acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxypropyl succinate, methacryloyloxypropyl succinate, acryloyloxyethyl phthalate, and methacryloyloxyethyl phthalate.
[0076] In the vinylidene fluoride copolymer used as a binder (C), from the viewpoint of improving the adhesion between the solid electrolyte and other devices (collector, active material, conductive aid, etc.), the content of the structural unit (Ca) derived from vinylidene fluoride is 90.0 mass% or more, preferably 95.0 mass% or more, and more preferably 98.0 mass% or more, when all the structural units contained in the vinylidene fluoride copolymer are set to 100.0 mass%.
[0077] In the vinylidene fluoride copolymer as the binder (C), the content of the structural units (Cb) derived from monomers other than vinylidene fluoride is not particularly limited, and for example, is preferably 0.01 mass % to 10.0 mass % relative to all the structural units in the vinylidene fluoride copolymer, more preferably 0.1 mass % to 5.0 mass % and further preferably 0.2 mass % to 2.0 mass %
[0078] The vinylidene fluoride copolymer may contain a structural unit (Cc) derived from a monomer different from the monomer providing the above-mentioned structural units (Ca) and (Cb) from the viewpoint of improving the adhesion between the solid electrolyte and other devices (collector, active material, conductive additive, etc.).
[0079] Examples of the other monomers include structural units derived from fluorine-containing monomers other than vinylidene fluoride and structural units derived from hydrocarbon monomers such as ethylene and propylene.
[0080] Examples of fluorine-containing monomers include vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, hexafluoroethylene, fluoroalkyl vinyl ethers, and perfluoroalkyl vinyl ethers represented by perfluoromethyl vinyl ether, etc. Among them, chlorotrifluoroethylene or hexafluoropropylene is preferred, and hexafluoropropylene is more preferred.
[0081] In the vinylidene fluoride copolymer as a binder (C), with respect to the content of the structural units derived from other monomers, when all the structural units contained in the vinylidene fluoride copolymer are set to 100.0% by mass, it is preferably 0.1% by mass or more and less than 10.0, more preferably 2.0% by mass or more and 8.0% by mass or less. In the case where the vinylidene fluoride device copolymer as a binder (C) contains the structural units derived from other monomers, from the viewpoint of improving the adhesion of the solid electrolyte to other (collectors, active materials, conductive aids, etc.), with respect to the content of the structural units (Ca) derived from vinylidene fluoride, when all the structural units contained in the vinylidene fluoride copolymer are set to 100.0% by mass, it is 90.0% by mass or more, preferably 91.0% by mass or more, and more preferably 92.0% by mass or more. The content of the structural unit (Cb) derived from a monomer other than vinylidene fluoride is preferably 0.01% by mass to 2.0% by mass, more preferably 0.1% by mass to 1.5% by mass, and further preferably 0.2% by mass to 0.8% by mass.
[0082] From the viewpoint of improving adhesion between the solid electrolyte and other devices (current collector, active material, conductive additive, etc.), the intrinsic viscosity of the vinylidene fluoride copolymer as the binder (C) is preferably 2.3 dL / g or more, more preferably 2.5 dL / g or more.
[0083] The content of the binder (C) is not particularly limited, but is preferably 1% by mass to 40% by mass, more preferably 2% by mass to 30% by mass, and further preferably 3% by mass to 20% by mass, relative to 100% by mass of the positive electrode active material layer.
[0084] (Method for producing adhesive (C))
[0085] The method for producing the binder (C) is not particularly limited, and is generally carried out by suspension polymerization, emulsion polymerization, solution polymerization, etc. From the viewpoint of ease of post-treatment, aqueous suspension polymerization and emulsion polymerization are preferred, and aqueous suspension polymerization is more preferred.
[0086] The aqueous suspension polymerization method is not particularly limited, and examples thereof include a method in which monomers used for polymerization are polymerized in an aqueous medium in the presence of a suspending agent, a polymerization initiator, a chain transfer agent, and the like.
[0087] The suspending agent is not particularly limited, and examples thereof include methylcellulose, methoxylated methylcellulose, propoxylated methylcellulose, hydroxyethyl methylcellulose, hydroxypropyl methylcellulose, polyvinyl alcohol, polyethylene oxide, gelatin, etc. The amount of the suspending agent used is not particularly limited, and for example, is preferably 0.005 parts by mass or more and 1.0 parts by mass or less, and more preferably 0.01 parts by mass or more and 0.4 parts by mass or less, relative to 100.0 parts by mass of all monomers used in the polymerization.
[0088] As polymerization initiator, it is not particularly limited, for example, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-n-heptafluoropropyl peroxydicarbonate, isobutyryl peroxide, di(chlorofluoroacyl) peroxide, di(perfluoroacyl) peroxide, and tert-butyl peroxypivalate etc. can be listed. The usage amount of polymerization initiator is not particularly limited, for example, relative to 100.0 mass parts of all monomers used in the polymerization, preferably more than 0.05 mass parts and less than 5 mass parts, more preferably more than 0.15 mass parts and less than 2 mass parts.
[0089] The chain transfer agent is not particularly limited, and examples thereof include ethyl acetate, propyl acetate, acetone, and diethyl carbonate.
[0090] In addition, the amount of monomers used in the polymerization is calculated as the mass ratio of the total monomers to water, which is usually 1:1 to 1:10, preferably 1:2 to 1:5. The polymerization conditions such as the polymerization temperature and polymerization time when performing suspension polymerization are not particularly limited, and for example, known polymerization conditions can be used. The polymerization temperature T can be appropriately selected based on the 10-hour half-life temperature T10 of the polymerization initiator, and is usually selected within the range of T10-25°C ≤ T ≤ T10 + 25°C. For example, the T10 of tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are 54.6°C and 40.5°C, respectively (refer to the product catalog of NOF Corporation). Therefore, when tert-butyl peroxypivalate and diisopropyl peroxydicarbonate are used as polymerization initiators for polymerization, the polymerization temperature T is selected within the range of 29.6°C ≤ T ≤ 79.6°C and 15.5°C ≤ T ≤ 65.5°C, respectively. The polymerization time is not particularly limited, and if productivity, etc. are taken into consideration, it is preferably 1 to 24 hours.
[0091] <Other ingredients>
[0092] As long as the effect of the present invention is not impaired, the positive electrode active material layer may also contain components other than the above-mentioned positive electrode active material (A), solid electrolyte (B) and binder (C) (hereinafter also referred to as "other components"). As other components, all known additives can be used, for example, conductive additives, insulating inorganic fillers such as aluminum oxide, magnesium oxide, and silicon dioxide, insulating organic fillers such as polytetrafluoroethylene, polyimide, and polyacrylonitrile, plasticizers such as ethylene carbonate, propylene carbonate, and ethyl methyl carbonate, LiPF 6 , Li salts such as LiFSI, LiTFSI, dispersants, flame retardants, defoaming agents, etc.
[0093] Examples of the conductive additive (D) include carbon black and carbon nanotubes, etc. These may be used alone or in combination of two or more.
[0094] The content of the conductive aid (D) is not particularly limited, but is preferably 0.05% by mass to 15% by mass, more preferably 0.1% by mass to 10% by mass, and further preferably 0.5% by mass to 8.0% by mass, relative to 100.0% by mass of the positive electrode active material layer.
[0095] "electrode"
[0096] The electrode is a positive electrode and includes a current collector and the positive electrode active material layer described above.
[0097] By including the positive electrode active material layer, the electrode exhibits an effect of suppressing the interface resistance between the current collector and the positive electrode active material layer.
[0098] (Current Collector)
[0099] The current collector is a terminal for taking out electricity. The material of the current collector is not particularly limited, and metal foil or metal mesh of aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc. can be used. In addition, it can also be a material formed by applying the above-mentioned metal foil or metal mesh on the surface of other media.
[0100] The volume density of the electrode is not particularly limited, but is preferably 1.5 g / cm 3 or more and 5 g / cm 3 or less, for example.
[0101] The weight per unit area of the electrode is not particularly limited, but is preferably 20 g / m 2 Above and 1000g / m 2 the following.
[0102] 《Electrode manufacturing method》
[0103] As a method for manufacturing an electrode, for example, there can be cited a method including the following steps: a step of mixing the above-mentioned positive electrode active material (A), solid electrolyte (B), binder (C), other components as required, and non-aqueous solvent (S) to prepare a positive electrode slurry; a step of applying the obtained positive electrode slurry to a collector and then drying it. That is, in the above-mentioned embodiment, after the step of drying the positive electrode slurry, the positive electrode active material layer is prepared, and the electrode is also prepared.
[0104] Examples of the non-aqueous solvent (S) include N-methyl-2-pyrrolidone (hereinafter referred to as "NMP"), dimethylformamide, N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N,N-dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate, acetone, cyclohexanone, methyl ethyl ketone, and tetrahydrofuran. These may be used alone or in combination of two or more.
[0105] The coating method is not particularly limited, and for example, a doctor blade method, a reverse roll method, a comma bar method, a gravure printing method, an air knife method, a die coating method, a dip coating method, and the like can be applied.
[0106] The drying temperature is, for example, preferably 80° C. or higher and 300° C. or lower, more preferably 90° C. or higher and 200° C. or lower, and further preferably 100° C. or higher and 180° C. or lower.
[0107] The drying time is, for example, preferably 10 seconds to 300 minutes, more preferably 1 minute to 200 minutes.
[0108] Drying can be performed multiple times at different temperatures. During drying, pressure can be applied.
[0109] All-solid-state battery
[0110] The all-solid-state battery includes the electrode of the above-described embodiment. As the all-solid-state battery, conventionally known components can be used for components other than the positive electrode, such as the negative electrode and the separator.
[0111] Semi-solid-state battery
[0112] The semi-solid battery has the electrode of the above embodiment. As a semi-solid battery, parts other than the positive electrode, such as the negative electrode, the separator, etc., can use previously known parts. When the volume of the electrolyte contained in the conventional secondary battery is set to 100%, the amount of electrolyte contained in the semi-solid battery is preferably 1% to 95%, more preferably 1% to 90%, and further preferably 1% to 80%.
[0113] Example
[0114] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0115] [Examples 1 to 5 and Comparative Examples 1 to 3]
[0116] <Materials used>
[0117] In the examples and comparative examples, the following A1 was used as the positive electrode active material (A).
[0118] A1: LiFePO 4 .
[0119] In Examples and Comparative Examples, the following B1 was used as the solid electrolyte (B).
[0120] B1: Li 1+x+y Al x Ti 2x Si y P 3y O 12 (LATP)(OHARA Corporation, "LICGC TM PW-01
[0121] (particle size 1 μm)”).
[0122] In the examples and comparative examples, the following C1 to C8 were prepared and used as the adhesive (C). In addition, the intrinsic viscosity of each prepared adhesive was measured by the following method.
[0123] In addition, the monomers used are as follows.
[0124] (1) Providing a monomer of a structural unit (Ca) derived from vinylidene fluoride:
[0125] Vinylidene fluoride (VDF).
[0126] (2) A monomer providing a structural unit (Cb) derived from a monomer other than vinylidene fluoride:
[0127] Monomethyl maleate (MMM) (unsaturated dibasic acid monoester).
[0128] Acryloyloxypropyl succinate (APS) (the compound represented by the above formula (C-2)).
[0129] (3) providing monomers of structural unit (Cc):
[0130] Hexafluoropropylene (HFP).
[0131] (Determination of intrinsic viscosity)
[0132] 80 mg of each binder was dissolved in 20 ml of N,N-dimethylformamide to prepare a binder-containing solution. Then, the viscosity η of the binder-containing solution was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. 1 Similarly, the viscosity η of N,N-dimethylformamide was measured in a 30°C constant temperature bath using an Ubbelohde viscometer. 0 Then, the intrinsic viscosity η was calculated based on the following formula.
[0133] Intrinsic viscosity η=(1 / C)·ln(η 1 / η 0 )
[0134] (Preparation Example of Adhesive C1 (VDF / HFP / MMM))
[0135] 240.2 parts by mass of ion exchange water, 0.2 parts by mass of methylcellulose, 97 parts by mass of vinylidene fluoride (VDF), 3 parts by mass of hexafluoropropylene (HFP), 0.3 parts by mass of monomethyl maleate (MMM), and 0.47 parts by mass of diisopropyl peroxydicarbonate (IPP) were added to a 2L autoclave and polymerized at 26°C. The obtained copolymer was heat treated at 95°C for 60 minutes, dehydrated, washed with water, and then dried at 80°C for 20 hours to obtain an adhesive C1. In the adhesive C1, 97.4% by mass of VDF, 2.3% by mass of HFP, and 0.3% by mass of MMM were contained relative to all structural units. The intrinsic viscosity (η) of the adhesive C1 was 3.1dL / g. It should be noted that the amount of each monomer in the adhesive C1 was determined as follows: the VDF / HFP ratio was calculated using 19-NMR, the VDF / MMM ratio was determined using the following method, and then the total of VDF, HFP and MMM was calculated as 100 mol%. The VDF / MMM ratio in the copolymer (the molar ratio of the amount of structural units derived from vinylidene fluoride to the amount of structural units derived from monomethyl maleate) was calculated based on the calculation method using the IR spectrum and the standard curve disclosed in WO International Publication No. 2009 / 084483.
[0136] (Preparation Example of Adhesive C2 (VDF / HFP / MMM))
[0137] The amount of ion exchange water was changed to 259 parts by mass, methyl cellulose was changed to 0.15 parts by mass, VDF was changed to 90 parts by mass, the amount of HFP was changed to 10 parts by mass, MMM was changed to 0.5 parts by mass, and IPP was changed to 0.5 parts by mass. In addition, VDF, HFP and MMM were polymerized by the same method as the preparation example of adhesive C1 to obtain adhesive C2. In adhesive C2, 92.5% by mass of VDF, 7.0% by mass of HFP, and 0.5% by mass of MMM are contained relative to all structural units. The intrinsic viscosity (η) of adhesive C2 is 2.6dL / g. (Preparation example of adhesive C3 (VDF / APS))
[0138] Adhesive C3 was obtained by polymerizing VDF and APS in the same manner as in the preparation example of Adhesive C1, using 231.3 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 99 parts by mass of VDF, 1.0 parts by mass of acryloxypropyl succinate (APS), and 0.5 parts by mass of IPP. Adhesive C3 contains 99.0% by mass of VDF and 1.0% by mass of APS relative to all structural units. The intrinsic viscosity (η) of Adhesive C3 is 2.5 dL / g. (Preparation Example of Adhesive C4 (VDF / HFP / APS))
[0139] Adhesive C4 was obtained by polymerizing VDF, HFP and APS in the same manner as in the preparation example of Adhesive C1 using 273 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 92 parts by mass of VDF, 2 parts by mass of HFP, 0.5 parts by mass of APS and 0.4 parts by mass of IPP. Adhesive C4 contains 94.1% by mass of VDF, 5.4% by mass of HFP and 0.5% by mass of APS relative to all structural units. The intrinsic viscosity (η) of Adhesive C4 is 2.1dL / g. (Preparation Example of Adhesive C5 (VDF / HFP / APS))
[0140] Adhesive C5 was obtained by polymerizing VDF, HFP and APS in the same manner as in the preparation example of Adhesive C1 except that 256 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 90 parts by mass of VDF, 10 parts by mass of HFP, 0.5 parts by mass of APS, 1.0 parts by mass of IPP and 0.22 parts by mass of ethyl acetate were used. Adhesive C5 contained 91.8% by mass of VDF, 7.7% by mass of HFP and 0.5% by mass of APS relative to all structural units. The intrinsic viscosity (η) of Adhesive C5 was 2.6 dL / g.
[0141] (Preparation Example of Adhesive C6 (PVDF))
[0142] Adhesive C6 was obtained by polymerizing VDF in the same manner as in the preparation example of Adhesive C1 except that 231.8 parts by mass of ion exchange water, 0.05 parts by mass of methylcellulose, 100 parts by mass of VDF, 0.7 parts by mass of IPP, and 0.7 parts by mass of ethyl acetate were used. Adhesive C6 contained 100.0% by mass of VDF relative to all structural units. The intrinsic viscosity (η) of Adhesive C6 was 2.1 dL / g.
[0143] (Production Example of Adhesive C7 (VDF / HFP / MMM))
[0144] VDF, HFP and MMM were polymerized by the same method as in the preparation example of adhesive C1, except that ion exchange water was changed to 290 parts by mass, methyl cellulose was changed to 0.0.1 parts by mass, VDF was changed to 85 parts by mass, HFP was changed to 15 parts by mass, MMM was changed to 0.5 parts by mass, IPP was changed to 0.9 parts by mass, and ethyl acetate was changed to 0.3 parts by mass, to obtain adhesive C7. Adhesive C7 contained 87.6% by mass of VDF, 11.9% by mass of HFP, and 0.5% by mass of MMM relative to all structural units. The intrinsic viscosity (η) of adhesive C7 was 1.3 dL / g.
[0145] (Production Example of Adhesive C8 (VDF / HFP))
[0146] VDF and HFP were polymerized by the same method as in the preparation example of adhesive C1, except that ion exchange water was changed to 253 parts by mass, methylcellulose was changed to 0.05 parts by mass, VDF was changed to 90 parts by mass, HFP was changed to 10 parts by mass, IPP was changed to 0.4 parts by mass, and ethyl acetate was changed to 1.0 parts by mass, to obtain adhesive C8. Adhesive C8 contained 93.0% by mass of VDF and 7.0% by mass of HFP relative to all structural units. In addition, the intrinsic viscosity (η) of adhesive C8 was 1.9 dL / g.
[0147] Table 1 shows the detailed information of the obtained adhesives C1 to C8.
[0148] [Table 1]
[0149]
[0150] In Examples and Comparative Examples, D1 described below was used as the conductive auxiliary agent (D).
[0151] D1: Carbon nanotube (CNT) dispersion.
[0152] In Examples and Comparative Examples, S1 described below was used as the nonaqueous solvent (S).
[0153] S1: N-methyl-2-pyrrolidone (NMP).
[0154] (Preparation of positive electrode slurry)
[0155] Each binder (C) is dispersed in N-methyl-2-pyrrolidone (NMP) at room temperature so that the concentration of the binder (C) becomes an arbitrary concentration, and then the solution temperature is raised to 50°C to dissolve each binder (C) (hereinafter referred to as "binder solution"). Using a positive electrode active material (A), a solid electrolyte (B), a conductive aid (D) and each of the above-mentioned binder solutions, each component is mixed in a manner of positive electrode active material (A) / solid electrolyte (B) / conductive aid (D) / binder (C) = 90 / 10 / 2 / 10 (mass %) to obtain each positive electrode slurry. The solid content of the positive electrode slurry is adjusted using NMP.
[0156] (Fabrication of positive electrode)
[0157] Each of the obtained positive electrode slurries was applied to an Al foil (thickness 15 μm), and then dried at 120° C. Each of the obtained preliminary positive electrodes was pressed and further heat treated at 120° C. for 3 hours. Thus, an electrode volume density of 2.3 g / cm 3 , weight per unit area is 200g / m 2 of each positive electrode.
[0158] <Evaluation>
[0159] The peel strength of each of the obtained positive electrodes was measured by the following method.
[0160] (Peel Strength)
[0161] Cut each positive electrode obtained into a size of 2.0cm×5.0cm, paste double-sided tape on the positive active material layer side of each positive electrode, adhere the positive active material layer to the acrylic plate, and pressurize at 4MPa for 20 seconds. Peel off half of the Al foil of the above positive electrode fixed on the acrylic plate, clamp it with a chuck, and measure it according to JIS K6854-1. The measurement conditions are head speed 10mm / min, distance between chucks 10mm, and measurement at 90°C peeling. The results are shown in Table 2.
[0162] [Table 2]
[0163]
[0164]
[0165] As can be seen from Table 2, in the positive electrodes of Comparative Examples 1 to 3 having a positive electrode active material layer comprising a binder C6 (PVDF) which is a homopolymer of vinylidene fluoride, a binder C7 (VDF / HFP / MMM) in which the structural unit (Ca) derived from vinylidene fluoride is less than 90% by mass, and a binder C8 (VDF / HFP) which does not contain a structural unit (Cb) derived from a monomer other than vinylidene fluoride, the maximum peel strength is only 67.4 gf / mm.
[0166] On the other hand, in the positive electrode active material layer comprising binders C1 to C5, the binders C1 to C5 contain structural units (Ca) derived from vinylidene fluoride and specific structural units (Cb) derived from monomers other than vinylidene fluoride, and the content of the structural unit (Ca) is more than 90% by mass. As shown in Examples 1 to 5, the minimum peel strength is 107.5 gf / mm, and it can be seen that the adhesion is greatly improved.
Claims
1. A positive electrode active material layer, comprising a positive electrode active material (A), a solid electrolyte (B) and a binder (C), wherein: The binder (C) is a vinylidene fluoride copolymer containing a structural unit (Ca) derived from vinylidene fluoride and a structural unit (Cb) derived from a monomer other than vinylidene fluoride, The structural unit (Cb) derived from a monomer other than vinylidene fluoride contains a structural unit derived from a compound selected from at least one of an unsaturated dibasic acid, an unsaturated dibasic acid monoester, and a compound represented by the following formula (C-1), When all structural units contained in the vinylidene fluoride copolymer are taken as 100.0 mass %, the structural unit (Ca) derived from vinylidene fluoride is 90.0 mass % or more, [Chemical formula 1] In formula (C-1), R 1 , R 2 and R 3 are independently a hydrogen atom, a chlorine atom or an alkyl group having 1 to 5 carbon atoms, X 1 It is an atomic group having a molecular weight of 472 or less, the main chain of which consists of 1 to 19 atoms, and contains at least one hetero atom selected from oxygen atoms and nitrogen atoms.
2. The positive electrode active material layer according to claim 1, wherein The intrinsic viscosity of the vinylidene fluoride copolymer is 2.3 dL / g or more.
3. The positive electrode active material layer according to claim 2, wherein The vinylidene fluoride copolymer contains a structural unit derived from hexafluoropropylene as a structural unit different from the structural unit (Cb), When all the structural units contained in the vinylidene fluoride copolymer are taken as 100.0 mass %, the structural unit derived from hexafluoropropylene is 2.0 mass % or more and 8.0 mass % or less.
4. The positive electrode active material layer according to any one of claims 1 to 3, wherein The structural unit (Cb) derived from a monomer other than vinylidene fluoride contains the structural unit derived from an unsaturated dibasic acid monoester, The unsaturated dibasic acid monoester is monomethyl maleate.
5. The positive electrode active material layer according to claim 1 or 2, wherein The solid electrolyte (B) is an oxide-based solid electrolyte.
6. The positive electrode active material layer according to claim 5, wherein The solid electrolyte (B) comprises a material represented by the following formula (B-1): Li 1+x+y Al x You 2x Yes y P 3y ON 12 ……(B-1) In formula (B-1), x and y satisfy 0≤x≤1, 0≤y≤1.
7. The positive electrode active material layer according to any one of claims 1 to 3, wherein The positive electrode active material (A) contains lithium metal phosphate, The lithium metal phosphate is selected from the group consisting of LiFePO 4 , LiMnPO 4 , LiCoPO 4 and LiNiPO 4 . 8 . An electrode comprising a current collector and the positive electrode active material layer according to claim 1 .
9. A semi-solid-state battery or an all-solid-state battery, comprising the electrode according to claim 8.
Citation Information
Patent Citations
Positive electrode active material layer for all-solid battery
JP2020113444A
Positive electrode active material layer for all-solid-state battery
JP2020126807A